The investment of spanish companies in latin america, patterns and determining features - Solana González, Gonzalo (2019)
The objective of this paper is to analyse the recent evolution of Spain’s Foreign Direct Investment in Latin America and the internationalization patterns of Spanish companies in these countries. To this end, statistics on investment flows have been studied and the main work of the authors in the business field have been reviewed. As a result, investment interest in Latin America has not decreased despite the crisis that began in 2008, due to its dynamism, the growth of its middle classes and the need to improve basic infrastructure. The interest in Latin America for the opportunities these countries offer to address third markets and improve competitive capacity is also noteworthy.